A Contribuição teórica do pensamento pedagógico de John Dewey para história e historiografia da educação brasileira: um estudo referente ao “estado da arte” da produção acadêmica (dissertação e tese) em programas de pós-graduação em educação. - Viana, Márcia de Brito (Universidade Federal do Tocantins, 2019)
This work aims to present a state of the art of the academic productions (dissertations and theses) of the Graduate School Programs in Education, in Brazil, produced between 1990 and 2015, on John Dewey's Pedagogical Thinking (1859-1952). For this, we divided this work into three chapters, in which the first one approaches the concepts of History and Historiography over time, in order to understand some questions about the state of the art. The second chapter presents the pedagogical thinking of the American philosopher, including the main categories studied by him, showing his importance as a philosopher and of his studies for Education. And finally, in the third chapter, we will analyze the data regarding the state of the art. During the realization of this research, we noted the relevance of this philosopher for the historiography of Brazilian education, due to the immense amount of academic products found that use his pedagogical thinking as a theoretical reference. Another aspect that was possible to know in this work was the Dewey categories that have been most used in these academic works. Therefore, this work is justified and becomes significant because of the rich information and analysis that this state of the art provides and because it also instigates our curiosity to a deeper look in this subject aiming to enter in the graduate school.